2017
DOI: 10.1111/dme.13362
|View full text |Cite
|
Sign up to set email alerts
|

Children's experiences of managing Type 1 diabetes in everyday life: a thematic synthesis of qualitative studies

Abstract: Although the synthesis has identified how children's everyday life experiences inform ways in which they undertake diabetes self-management, it was not possible to determine new ways to provide support. To help children optimise their glycaemic control, further work should be undertaken to identify their need for support and which takes into account the potential ways in which parents, friends and peers can offer assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 43 publications
2
23
1
2
Order By: Relevance
“…Children also highlighted the upset, distress and isolation they experienced as a consequence. For this reason, and in keeping with findings reported in other studies, children described preferring to interact with, and accept support from, a small number of friends who wanted to help and were interested in learning about diabetes. These friends, as children reported, had often developed knowledge about diabetes by asking questions opportunistically and when observing them perform self‐management tasks, which then enabled them to provide three overlapping types of support as “monitors and prompters,” “helpers” and “normalizers.” While valuing this practical and emotional input from selected friends, children reported more mixed and ambivalent views about receiving support from peers with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Children also highlighted the upset, distress and isolation they experienced as a consequence. For this reason, and in keeping with findings reported in other studies, children described preferring to interact with, and accept support from, a small number of friends who wanted to help and were interested in learning about diabetes. These friends, as children reported, had often developed knowledge about diabetes by asking questions opportunistically and when observing them perform self‐management tasks, which then enabled them to provide three overlapping types of support as “monitors and prompters,” “helpers” and “normalizers.” While valuing this practical and emotional input from selected friends, children reported more mixed and ambivalent views about receiving support from peers with type 1 diabetes.…”
Section: Discussionsupporting
confidence: 82%
“…We have also highlighted how children can feel distressed when they encounter peers who, because they do not understand diabetes, can act in seemingly insensitive, inappropriate and unsupportive ways. Other studies have shown that children with diabetes can be vulnerable to bulling by friends and peers and although children in our study did not explicitly state having been bullied, their accounts suggest that this experience cannot be discounted. While some close friends do appear to be capable of understanding diabetes and ways to manage the disease, we would suggest that the problems our participants described are unlikely to be the result of their wider peer group being unable to comprehend and apply diabetes learning.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…The notion of health practices challenges the assumption that health is a direct outcome of mental processes and implies that it emerges from interactions between individuals, as well as social and material factors. Rankin et al (, 2018) find that preteens altered their care practices across family and school settings and that they disliked how diabetes distinguishes them from others, causing unwanted attention (Rankin et al, ; Rankin, Harden, Jepson, & Lawton, ). These findings highlight the importance of social practices in shaping diabetes care and suggest the relevance of applying a broad conceptualization of preteens' social relations, which is not limited to their relationships with parents.…”
Section: Discussionmentioning
confidence: 99%
“…The databases were searched for papers published between 1995 and March 2018. This time range was based on previous systematic reviews in the field (Ayling, Brierley, Johnson, Heller, & Eiser, ; Rankin, Harden, Jepson, & Lawton, ).…”
Section: Methodsmentioning
confidence: 99%